ANALISA MANAJEMEN WAKTU PENJADWALAN PROYEK KONSTRUKSI PEMBANGUNAN DERMAGA MENGGUNAKAN METODE ACTIVITY ON NODE (AON) (Studi Kasus Pembangunan Dermaga Desa Pulau Burung Kecamatan Pulau Burung Kabupaten Indragiri Hilir Tahun Anggaran 2018) - Muhammad Risman Akbar Alfa (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Progress in industrial activities in some aspects requires management or management that is demanded to have performance, accuracy, economics, integration, speed, accuracy, high security accuracy in order to obtain the final results as expected. The technology of the construction industry is currently driven to balance both the technical and management aspects, from the technical point of view the parties involved try to make or formulate a careful calculation, while in terms of management try to make an efficient and effective method so that a good plan can be implementation of construction projects Project is a temporary activity that has clear goals and objectives, takes place in a limited period of time with the allocation of certain resources. Data processing is done using the AON (Activity On Node) method, the duration of the previous activity is 120 working days, after processing data with the AON method, the duration of the activity is shortened to 95 working days where the time saved is 25 days.